A review on tin slag polymer concrete as green structural material for sustainable future - Muhamad Soffi, Manda; Mohd Ruzaimi, Mat Rejab; Shukur, Abu Hassan; Quanjin, Ma (Springer Nature, 2021)
Ordinary Portland cement concrete (OPC) is widely utilized in construction industry as structural material, but it has environmental issue due to natural resources consumption and Carbon emission. Therefore, polymer concrete (PC) with tin slag (TS) waste are introduced to replace aggregate and cement in OPC. Previous research on potential to apply TSPC as structural material has provided compressive strength data which shows that it can compete with OPC. PC using polyester and 100% TS aggregate with resin-aggregate ratio 30:70 consist of fine ([removed]